A Snapshot of China's Service Sector - Molnar, Margit (OECD Economics Department Working Papers, 2015)
The share of the tertiary sector in China's value added has increased steadily, overtaking the share of the secondary sector in 2013. With increasing incomes, the share of services is expected to grow further as at higher incomes a larger share of income is spent on services. In addition to final demand, intermediate demand can be another driving force for service industries. As liberalisation leads to a greater role for the market in allocating resources, service industries are expected to become more competitive and therefore it may become cheaper to outsource services than to produce them in-house. Liberalisation will likely also lead to greater specialisation to remain competitive, thereby making specialised services available for outsourcing. This will likely spur the development of some high value-added logistics services such as warehousing or order handling. By the same token, professional services such as accounting or engineering are also likely to benefit from a greater reliance on the market and greater competition. In the envisaged transition from "made in China" to "created in China", the service sector is expected to play a prominent role. To that end, the service sector is gradually being provided a more even playing field as privileges for manufacturing industries are being withdrawn and a more equal treatment of producers across sectors is being adopted. This paper provides a snapshot of the service sector, its size, the ownership of its firms, and productivity across types of firms depending on ownership, sector, age, size and geographical region. This Working Paper relates to the 2015 OECD Economic Survey of China www.oecd.org/eco/surveys/economic-survey-china.htm